Hydrogen production, separation and purification for energy - Basile, Angelo; Dalena, Francesco; Tong, Jianhua; Veziroğlu, T. Nejat (The Institution of Engineering and Technology, 2017)
The following topics are dealt with: hydrogen production; reforming process; catalysts; supercritical water gasification; biofuels; fixed bed membrane reactors; micromembrane reactors; perovskite membrane reactors; hydrogen separation; and carbon-based membranes.
Keywords: Hydrogen as fuel.; Hydrocarbons.; elektronické knihy; electronic books